ANALISIS PENERAPAN AKUNTANSI AKTIVA TETAP SESUAI DENGAN PSAK NO. 16 PADA PT. AGRO TUMBUH GEMILANG ABADI - Rebecca Evadine (LP2MTBM MAKARIOZ, 2018)
Fixed assets have an important role for the smooth operation of the company. Necessary to maximize the role of the appropriated policy in the management of fixed assets. In these circumstances, the decision makers are going to need a tool of information on fixed assets are fixed assets accounting. This study aims to assess the extent to which the company has implemented a fixed asset accounting policies are consistent with the theory, which based on Statement of Financial Accounting Standards (SFAS) no. 16 in company activities.The approach used in this study is qualitative approach with descriptive research.. From the results of this study were concluded that the PT. Agro Tumbuh Gemilang Abadi in the course of accounting based on the Company's accounting policies that have led to SFAS. 16 on fixed assets. In practice, companies distinguish the type and manner of acquisition of fixed assets is by cash purchase, build their own way and etc., the company shrink its fixed assets using the Straight Line method in which it is in accordance with the applicable Accounting Standards, the company discontinue fixed assets that are not used mainly by way of removing assets from the ownership. As well as the presentation and disclosures, the company reports financial statements are in accordance with the pattern of Financial Accounting Standards